P-118 Timed Intercourse exacerbates the risk of sexual dysfunction in men & women without an improvement in time to pregnancy. (30th June 2022) - Abdel-Latif, M; Nyantakyi, A; Frodsham, L.C; Patra, P; Chanda, A; Yap, T; Dasgupta, S
Abstract: Study question: Investigate the differences in sexual dysfunction and time to pregnancy between infertile couples pursuing timed intercourse and Regular Intercourse (RI at least twice a week). Summary answer: TI significantly increased the risk of SD compared to RI for both males and females after adjusting all other contributing factors. What is known already: Timed Intercourse (TI) involves aligning sexual intercourse to the time around ovulation to increase the chance of conception in couples trying to conceive. Whilst TI is often advocated to increase conception rates and potentially accelerate the time to pregnancy (TTP) for infertile couples, the stressful nature of this approach may be associated with adverse effects such as sexual dysfunction (SD) within the couple. Study design, size, duration: This prospective cohort study recruited 371 infertile couples who had been trying to conceive for more than a year, presenting to three regional infertility clinics between January 2016 and December 2018. 283 couples pursued TI and 88 couples pursued RI for a year, with all couples having no pre-existing sexual or psychiatric illness, and no medical contraindications to frequent intercourse. Participants/materials, setting, methods: The SD score of both partners was assessed at the first visit using the validated Arizona Sexual Experiences Scale (ASEX) and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V). TTP was determined using Kaplan Meier Analysis in couples for whom natural conception was possible and no reversible fertility pathology was identified. Main results and the role of chance: Timed Intercourse (TI) involves aligning sexual intercourse to the time around ovulation to increase the chance of conception in couples trying to conceive. Whilst TI is often advocated to increase conception rates and potentially accelerate the time to pregnancy (TTP) for infertile couples, the stressful nature of this approach may be associated with adverse effects such as sexual dysfunction (SD) within the couple. TI significantly increased the risk of SD compared to RI for both males (Odds ratio [OR] 15.24, 95% confidence interval [CI] 7.96-29.15) and females (OR 5.52, 95% CI 2.38- 12.78), after adjusting for age, medical disorders, obesity, smoking, cause of infertility, and previous assisted reproductive techniques. TI carried a higher risk of developing erectile dysfunction, premature ejaculation, male hypoactive sexual dysfunction, female sexual interest-arousal disorder, and female orgasmic disorder. The TTP for natural conception was similar between TI and RI (p = 0.1365). Limitations, reasons for caution: TI, a well-known strategy for increasing conception rates, did not improve time to natural conception compared to regular sexual intercourse. In contrast, the risk of sexual dysfunction in both men and women was significantly higher in TI, compared with RI. Wider implications of the findings: This large study raises the question of effectiveness of the long-held belief that TI (intercourse limited around the ovulation-time, based on different methods of ovulation-prediction) improves pregnancy outcomes. Trial registration number: N/A